Life writing as literary relic: image, inscription and consecration in Tibetan biography - Quintman, Andrew (Material religion, 2013)
This article addresses a largely unstudied form of writing inked on the rear face of Tibetan hanging scroll paintings. These are consecration inscriptions consisting of Buddhist mantras and other ritual formulas, and serve to ritually transform the image from static representation into a living manifestation of its subject. Since at least the eleventh century in Tibet, such inscriptions were composed as shaped texts, crafted in the form of a Buddhist reliquary or stūpa. In such cases, I suggest that the process of "entombing" a literary relic within an inscribed stūpa visually copies the ubiquitous Buddhist practice of interring corporeal relics inside three-dimensional monuments. In particular, this article examines a special form of shaped consecration inscription that replaces basic ritual formulas with biographical texts describing the life and qualities of the painted subject. It argues that such a text embodies its subject both literally and literarily, creating individuated relics that encapsulate not only the subject's body but the entire range of his enlightened activities as well. The essay questions received notions about the forms and functions of Tibetan biographical literature by shifting from a strict analysis of narrative content toward an emphasis on the material forms of individual texts.